Regional and Sectoral System for Integrated Assessment and Green Supply Chain Management of Natural Resources - Svetlana Alexandrovna Chernyavskaya; Albina Konstantinovna Berkaeva; Svetlana Akhmetovna lyanova; Kashukoev Murat Vladimirovich; Valery Safarbievich Misakov (International Journal of Supply Chain Management, 2020)
Abstract- Initially, any economic activity is associated with a negative impact on the environment. In modern realities, this situation requires mandatory preliminary assessment of an investment project in order to prevent or at least minimize the negative impact on the territory. In this regard, one of the urgent tasks of sustainable development in the territory is using green supply chain management (GSCM) to improve the system of strategic management and analysis of investment projects in order to identify the main reasons for its improper functioning. In accordance with the principles of system analysis, all kinds of complex problems that constantly arise in front of society (first of all, the problem of strategic management) must be considered in a holistic context, in the form of a system of interaction between all its components, as a rule, such as an organization of components focused on a single goal. However, due to the fact that in everyday practice, real systems are more complex, they prefer to use those models for the purposes of system analysis, that reflect the studied properties of real systems in a certain approximation. Any investment project can be considered not only as exclusive project documentation, but also as a set of economic relations that arise between many participants: subsoil users, the public, government agencies, and the environment itself. Moreover, these relationships are manifested at all stages of the investment project's life cycle from the design and implementation processes to its liquidation. The methodological approaches of cybernetics and system analysis are effectively used to understand the behavior of such organizational systems. In the theory of effective environmental management, there is still no proper reflection of the problems concerning qualitative and quantitative research of material and energy flows, the flow of pollution of natural objects, through which the interaction between productive forces and environmental systems takes place. All this, of course, shows the relevance and importance of developing new criteria for ecological and economic systems.